2005
DOI: 10.1042/bst20051096
|View full text |Cite
|
Sign up to set email alerts
|

Expression and activity of β-site amyloid precursor protein cleaving enzyme in Alzheimer's disease

Abstract: Several lines of evidence indicate that the Abeta peptide is involved at some level in the pathological process that results in the clinical symptoms of AD (Alzheimer's disease). The N-terminus of Abeta is generated by cleavage of the Met-Asp bond at position 671-672 of APP (amyloid precursor protein), catalysed by a proteolytic activity called beta-secretase. Two 'beta-secretase' proteases have been identified: BACE (beta-site APP-cleaving enzyme) and BACE2. The cause of sporadic AD is currently unknown, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 53 publications
1
15
1
Order By: Relevance
“…Previous studies have revealed an increase in b-secretase activity in postmortem brain tissue, CSF and platelets in AD (Johnston et al 2005Stockley et al 2006;Zhao et al 2007). Our previous work found no significant correlation between platelet membrane b-secretase activity and cognitive decline (MMSE score) .…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have revealed an increase in b-secretase activity in postmortem brain tissue, CSF and platelets in AD (Johnston et al 2005Stockley et al 2006;Zhao et al 2007). Our previous work found no significant correlation between platelet membrane b-secretase activity and cognitive decline (MMSE score) .…”
Section: Discussionmentioning
confidence: 96%
“…Blood platelets can be an important additional source of Aβ in the brain, especially in Aβ accumulation around blood vessels, since Aβ is directly released by platelets [2, 7] or cleaved from platelet-released APP. APP, in turn, is cleaved immediately after release by APP-cleaving enzyme 1 (BACE1), located on the platelet membrane [48, 49], or by the endothelial cells of brain blood vessels [50]. MOAB-2 [NBP2-13075] (mouse IgG2b), the anti-Aβ antibody used in this study, was extensively examined previously and was found to be a pan-specific, high-titer antibody to Aβ residues 1–4, reacting with unaggregated, oligomeric, and fibrillar forms of Aβ42 and unaggregated Aβ40 as well as with aggregated amyloid in plaques [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…MOAB-2 [NBP2-13075] (mouse IgG2b), the anti-Aβ antibody used in this study, was extensively examined previously and was found to be a pan-specific, high-titer antibody to Aβ residues 1–4, reacting with unaggregated, oligomeric, and fibrillar forms of Aβ42 and unaggregated Aβ40 as well as with aggregated amyloid in plaques [51,52]. MOAB-2 anti-Aβ antibody did not detect APP or its derivatives and did not colocalize with antibodies to either N- or C-terminal APP [49]. …”
Section: Discussionmentioning
confidence: 99%
“…Overexpression or downregulation of BACE1 induces or inhibits APP processing and Aβ generation both in vitro and in vivo [81-85]. Several studies find that BACE1 level and activity are elevated significantly in AD brain [86,87]. In addition, in an APP overexpression AD mouse model, deletion of BACE1 can abolish Aβ pathology and rescue cholinergic dysfunction and memory deficits [88-90].…”
Section: Introductionmentioning
confidence: 99%